Física sensorial: uma proposta para o ensino de termologia a videntes e deficientes visuais - Gonçalves, Camilo José Gonzaga (2019)
Physics in high school is, by many, rated as difficult subject and this arouses in some students an aversion to discipline. The difficulty in understanding may be due to the lack of mastery of content and thus of mathematical formalism. These factors are even greater if we consider the teaching of the visually impaired, due to the lack of reference in the context of contextualization and application in daily life. The teaching proposal present in this work aims at a conceptual approach of High School Thermology with low cost tactile 3D educational resources (mockups) that can compensate for blind or low vision students' lack of vision (if there are any in the classroom) but which can be used without any limitation for regular students. For through them it is possible to demonstrate molecular interactions present in images in textbooks in a manageable and interactive way. The materials were used with blind people and seers on different occasions, the qualitative and quantitative results after their application point to good performance and utilization, and thus become relevant for the construction of knowledge when used as support for common teaching materials.